Mobile application development of IoT-based broiler chicken feeding system - Muhammad Agung Laksono; Purba Daru Kusuma; Randy Erfa Saputra (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2023)
In this research, an Android application was developed using the React Native framework, integrated with Firebase, and the Arduino Mega 2560 microcontroller with built-in Wi-Fi to control and monitor the automated, scheduled, and real-time feeding and cleaning processes for chicken waste. This setup allows the utilization of an ultrasonic sensor to detect feed capacity and real-time scheduling. Additionally, a servo motor is used to automate the feeding system. The application enables farmers to monitor the feeding schedule adherence. Therefore, features such as feed system monitoring, alarm system, automatic cleaning system, and system status monitoring are included in this application. The test results demonstrate that this Android application functions well and provides accurate information to farmers. Users can remotely control the system, monitor the system's condition, and efficiently manage the feeding schedule. With the implementation of this application, it is expected that farmers can enhance productivity and efficiency in broiler chicken farming.